Task-Oriented Leadership and Employee Performance: A Case Study of Buhoma Mukono Community Development Association (BMCDA) in Kanungu, Uganda - Orikyiriza, Elli; Moses, Agaba; Alex, Kanyesiime (Science Publishing Group, 2022)
The study aimed to determine the relationship between Task-oriented Leadership and Employee Performance at Buhoma Mukono Community Development Association (BMCDA). The study objectives were: to determine the relationship between task structure and employee performance; to investigate the influence of level of authority on employee performance at BMCDA; and, to examine the influence of leader-member relations on employee performance at BMCDA. The study employed a cross-sectional research design using both quantitative and qualitative approaches. The target population of the study was 120 respondents. Ninety-two (92) respondents were selected using simple random sampling, and 12 key informants (leaders/managers) were selected using purposive sampling. Subsequently, the researcher used questionnaires and interview methods to collect data from respondents. The study findings revealed a correlation coefficient of r = .682 which shows a significant relationship between task structure and employee performance. The study findings also revealed that there was a significant relationship between the level of authority and employee performance as indicated by a correlation coefficient of r = .490. The study findings revealed a weak correlation coefficient of r = .171 which implies a weak positive relationship between leader-member relations and employee performance. The conclusion of the study, therefore, was that task-oriented leadership has a more significant positive relationship with employee performance, in which situation leader’s behaviour which involves: inspiring a shared vision through timely communication, emphasizing development and recognizing accomplishments explain some of the determinants in whether employees will ensure timeliness, quality, the quantity of work and cost-effectiveness at BMCDA. The researchers recommend that a more significant and more positive focus should be put on leadership behaviour that involves giving constructive feedback about performance, providing resources to employees to help them accomplish tasks, and implementing procedures to improve work processes, to improve employee performance. Such changes should be properly and carefully implemented to guide, and motivate subordinates and ensure organizational effectiveness.